Citizenship processes in the construction of political subjectivities: a theoretical approach - Herrera, Steven (Facultad de Ciencias Políticas y Sociales, 2020)
The current article intends to approach the process of citizenship from the perspective of critical psychology (more specifically, liberation psychology of second generation). In order to achieve this, it is firstly necessary to problematize the current scopes and limitations of psychology disciplinary approaches to this field. Secondly, we will reflect on new epistemological and theoretical views which may be useful in the construction of a theoretical framework that addresses the citizenship problem from a psycho-political perspective.